A escravidão segundo a ótica de Jesus: uma reflexão a partir da Teologia da Missão Integral segundo Mateus 20.20-28 - Machado, Cláudio Araújo (2022)
This dissertation presents an exegesis of Mt 20.20-28, in which the mother of the sons of Zebedee asks Jesus for places of status for the two sons, in the kingdom that would be established. The fact that occurred while walking to Jerusalem offers the opportunity for Jesus to teach about the principles of relationships in the alternative society or kingdom of God. Jesus condemns the form of relationship that is exercised in pagan governments, where there is violent oppression and tyranny and presents the ideal condition for citizens who integrate the Kingdom of God, to be servants and slaves. The objective of the dissertation is to analyze the context of the institution of slavery and identify the position of Jesus on this topic. The exegetical method used is historical-critica